Legal Relationship between Go-Jek Drivers and PT Go-Jek Indonesia in the E-Contract Partnership (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to analyze the legal relationship of the e-contract partnership with Go-Jek drivers. The legal issue that is the focus of this study identifies and analyzes the legal relationship between Go-Jek drivers and PT Go-Jek Indonesia in a partnership agreement in the form of e-contract. This research method is normative considering the existence of legal obscurity related to the partnership e-contract arrangement. The research approach used is the Legislative Approach and the Conceptual Approach. With the pattern of equal cooperation in partnership, the reality is that the legal relationship between PT Go-Jek Indonesia and the Go-Jek driver has been inequality. Therefore, the Go-Jek driver as a legal subject becomes weak and needs legal protection. Moreover, the partnership as outlined in the e-contract has not fully provided preventive and repressive legal protection.